Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.nicl.2019.101744
|View full text |Cite
|
Sign up to set email alerts
|

Applying surface-based hippocampal morphometry to study APOE-E4 allele dose effects in cognitively unimpaired subjects

Abstract: Apolipoprotein E (APOE) e4 is the major genetic risk factor for late-onset Alzheimer's disease (AD). The dose-dependent impact of this allele on hippocampal volumes has been documented, but its influence on general hippocampal morphology in cognitively unimpaired individuals is still elusive. Capitalizing on the study of a large number of cognitively unimpaired late middle aged and older adults with two, one and no APOE-e4 alleles, the current study aims to characterize the ability of our automated surface-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 98 publications
6
59
1
Order By: Relevance
“…Demographic information for the Arizona APOE cohort and ADNI cohort are summarized in Table 1 . Within each cohort, group differences of gender and APOE-ε4 genotype were estimated using chi-square tests, group differences of age and education were calculated by t -tests ( Crivello et al, 2010 , Dong et al, 2019 ). Inferential analysis demonstrated that the CU progressors and non-progressors have no significant differences on sex, age, education, and relevant APOE genotype.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Demographic information for the Arizona APOE cohort and ADNI cohort are summarized in Table 1 . Within each cohort, group differences of gender and APOE-ε4 genotype were estimated using chi-square tests, group differences of age and education were calculated by t -tests ( Crivello et al, 2010 , Dong et al, 2019 ). Inferential analysis demonstrated that the CU progressors and non-progressors have no significant differences on sex, age, education, and relevant APOE genotype.…”
Section: Resultsmentioning
confidence: 99%
“…After we calculated the significant variations on the ventricular surface, we could apply directional analysis ( Yao et al, 2018 , Dong et al, 2019 ) to study the correspondence between VV enlargement and ventricular morphometry expansion. The direction (atrophy or expansion) of group differences were analyzed along the surface normal direction and within surfaces at each surface point.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations